In vivo evaluation of the toxic and genotoxic effects of exposure to cobalt nanoparticles using Drosophila melanogaster. Issue 2 (13th January 2020) - Alaraby, Mohamed; Demir, Esref; Domenech, Josefa; Velázquez, Antonia; Hernández, Alba; Marcos, Ricard
Abstract : Nanomaterials in general and cobalt nanoparticles (CoNPs) in particular are of great interest not only because of their multiple applications and environmental impact, but also for their potential toxicity and safety issues. Abstract : Nanomaterials in general and cobalt nanoparticles (CoNPs) in particular are of great interest not only because of their multiple applications and environmental impact, but also for their potential toxicity and safety issues. Since most of the mechanisms involved in the toxicity of CoNPs are not very well known, mainly in vivo, we used Drosophila melanogaster as a simple and reliable in vivo model to investigate some toxicity-involved mechanisms. Thus, several toxicity-related approaches are used in this study including physicochemical characterization, viability, internalization, intracellular oxidative stress, and DNA damage (comet assay). In addition, changes in the expression of genes involved in general stress and antioxidant response, as well as in DNA repair response were evaluated, to better understand the underlying molecular mechanisms. The effects of CoNPs were compared with those induced by cobalt chloride (CoCl2 ), as a model ion releasing agent, to determine the role of the nanosized shapes in the observed responses. The obtained results indicate that ingested CoNPs translocate through the intestinal barrier of Drosophila larvae affecting hemolymph cells. Hemocytes, as targeted cells, show higher levels of intracellular reactive oxygen species (ROS) after CoCl2 exposure, but lower levels of DNA damage, in comparison with those induced by CoNPs. In addition, different genes showed an altered expression pattern, accordingly, if larvae were exposed to CoCl2 or to CoNPs. Subsequently, the effects induced by CoNPs cannot be associated only with their chemical nature.